(untitled) (Raparin Journal of Humanities (RJH), 2022)
Pragmatism, a philosophical approach that originally appeared in the USA, places its evaluation of the validity of ideas on concepts such as "action" and "benefit". The pioneers of this philosophy believe that the basis of human thought and knowledge should be traced back to the notion of benefit. Language, according to John Dewey, is a tool for representing thought and meaning. Accordingly, the language must be loaded with utilitarian ideas and be a tool for creating a practical and realistic effect. That is, pragmatism was concerned with the purpose of language use and its significance at the expense of its form. It is worth mentioning that some other branches in linguistics were born from pragmatism, such as pragmatics, which deals with language in use, semiotics, applied linguistics, behaviorism, speech act theory, and discourse analysis. All of these branches of linguistics are concerned with the actual and utilitarian aspects of language and investigate language in terms of usage and conditions of use. This paper is an attempt to highlight how these linguistic fields are affected by the philosophy of pragmatism. The research consists of two sections. In the first section, the broad outlines of the philosophy of pragmatism are examined, and in the second section, the effect of the pragmatism philosophy on these fields of linguistics is examined.